A REPRESENTAÇÃO DO PAPEL DE GOVERNANTAS/BABÁS EM EMMA, DE JANE AUSTEN, E SUÍTE TÓQUIO, DE GIOVANA MADALOSSO - GIOVANNA STAEL DE ABREU DOS SANTOS (2024)
This study aims to analyze the representation of the role of governesses/nannies and their invisibility within fictional works and in reality, from a feminist perspective. To this end, two characters will be examined: Miss Taylor, from Emma (1815) by Jane Austen, and Maju, from Suíte Tóquio (2020) by Giovana Madalosso, with a focus on understanding how these characters become protagonists in their narratives. Miss Taylor/Mrs. Weston is the governess of the Woodhouse family, while Maju works as a nanny for Fernanda and Cacá. The characters share similarities in their portrayal as maternal figures to the children they care for; however, they differ in their levels of protagonism, suggesting an evolution from one work to the other. This analysis investigates the representation of governesses/nannies as maternal figures, the (in)visibility of the characters Maju and Miss Taylor, and their respective portrayals in these works. It draws on the theoretical frameworks of Aristotle in The Poetics (2021) and Erich Auerbach in Mimesis (2021). Additionally, a historical analysis is conducted to assess the verisimilitude of these portrayals, using insights from Eu, empregada doméstica (2019) by Preta-Rara and discussions from Trabalho Doméstico (2021) by Juliana Teixeira, in dialogue with contemporary issues. The study ultimately examines the societal role imposed on women, informed by Silvia Federici's works, Caliban and the Witch (2017) and Revolution at Point Zero (2019).